Gloves holes defect evaluation by using electronic air leak testing machine - Md Din, Mohd Lizan (2017)
Process variation in gloves manufacturing is one of major problem which is deviating the levels of quality. It is becoming more challenging than before especially in the medical gloves manufacturing area. The demand for a higher quality gloves product is getting tougher to meet and new technology to fulfill the demand is needed to meet the extended requirement. The method of confirming gloves product quality through sampling and AQL levels is getting more costly as it could lead to false sampling which extended to severe customer complaint and disastrous product recall. A higher technology with 100% product inspection is essential to ensure the gloves produced is 100% free from defects. The purpose of this research is to provide a better assurance of product before shipped to customer by eliminating the sampling size method and replace it with a 100% inspection method .A machine was developed by a machine manufacturer which is called Leak Test Machine to sort out defected gloves with pin holes. Initially, method used to sort out defect and good gloves from a container (±4000 pieces) is by using pressure to inflate the gloves, pressure differential of initial test value compared to finished test value will be counted through designated time given. A set point which sets as a border line between defect value and accepts value is determined by operator through series of validation but due to the process variation, the properties of gloves will not be exact in term of tensile strength, elongation and thickness. This will lead to either rejecting good gloves or accepting defect gloves. To reduce the uncertainties of defect / accept gloves from those variations, a research to analyze the efficiencies of those two methods will be studied .It is expected that the Leak Test Machine with 100% inspection method, is capable of conducting the gloves pinhole test with the same capability or better than the Water Leak Test method by measurement and analysis through this research. Through the research performed, it is concluded that by using the Pneumatic Leak Test machine through 100% inspection, it is expected to screen out defect at 37 % better than the Water Leak Test through AQL sampling.